GOaL” LITERATURE MOVEMENT AS A MEANS OF IMPROVING LITERACY IN INSTRUCTION COMMUNITIES OF DUSUN III SRI PENGANTIN KEC. STL ULU TERAWAS KABUPATEN MUSI RAWAS - Fitria; Andriansah, Agus; Lestari , Sinta Bella; Putri, Nadia Sah; Asmara, Puja Ayu Intan; Octaline, Selvia; Nuryani, Intan; Karyono, Hendra; Pratama, Frengky Alexander; Af’idah, Euis Nur; Ananda, Septi; Padli, Kokoh; Sari, Bella Anggun; Akbar, Rinaldi; Wijaya, Gusti Aldo; Rida (Indra Institute Research & Publication, 2022)
Dusun III Sri Pengantin is a hamlet located in STL Ulu Terawas Subdistrict, Musi Rawas Regency with a location and access that can only be using “ketek”. Due to difficult access, education, adn motivation to learn is also minimal, this is also coupled with the lack of teachiers in the hemlet. The existence of these problems is also the cause of low literacy skills among children, adolescents, and the elderly. Therefor, one way is to carry out the “GOaL” literacy Omah movement by creating 5 literacy in the hamlet Dusun III Sri Pengantin. The methodu used is socialization, implementation, and evaluation. The result of this activity is that there is an increase in literacy skills. This increase can be seen from the literacy ability which was initially still lacking, has increased in terms of the results of the autobiography made. The conclusion that can be drawn is that the existence of the “GOaL” means to help improve the literacy skilla of the inland community of Dusun III Sri Pengantin.